To find the difference \( \sqrt{8125} - \sqrt{780} \), we first simplify each square root.
-
Simplifying \( \sqrt{8125} \): \[ 8125 = 25 \times 325 = 25 \times 25 \times 13 = 625 \times 13 \] Thus, \[ \sqrt{8125} = \sqrt{625 \times 13} = \sqrt{625} \cdot \sqrt{13} = 25\sqrt{13} \]
-
Simplifying \( \sqrt{780} \): \[ 780 = 4 \times 195 = 4 \times 3 \times 65 = 4 \times 3 \times 5 \times 13 \] Therefore, \[ \sqrt{780} = \sqrt{4 \times 195} = \sqrt{4} \cdot \sqrt{195} = 2\sqrt{195} \]
Now, we need to combine these two results: \[ \sqrt{8125} - \sqrt{780} = 25\sqrt{13} - 2\sqrt{195} \]
Next, simplify \( \sqrt{195} \): \[ 195 = 3 \times 5 \times 13 \] So, \[ \sqrt{195} = \sqrt{3 \times 5 \times 13} = \sqrt{3} \cdot \sqrt{5} \cdot \sqrt{13} = \sqrt{15 \cdot 13} \]
Now we can rewrite \( 2\sqrt{195} \) as: \[ 2\sqrt{195} = 2\sqrt{3 \cdot 5 \cdot 13} \]
Thus, our original expression \( 25\sqrt{13} - 2\sqrt{195} \) remains: \[ 25\sqrt{13} - 2\sqrt{195} = 25\sqrt{13} - 2\sqrt{15 \cdot 13} \]
To find a numeric approximation:
- Calculate \( \sqrt{13} \) using a calculator or estimation.
- Approximate \( 25\sqrt{13} \) and \( 2\sqrt{195} \).
As we compare, the best match will be one of the given responses. After calculations: \[ \sqrt{8125} - \sqrt{780} \approx 35 - \sqrt{5} \]
Thus, based on the provided options, the closest answer representing \( 8125−−−√−780−−−√ \) is: 35 – √5.